La interdisciplinaridad como metodología de aprendizaje para vincular la Zoología con la Microbiología en los estudiantes de cuarto semestre de la Carrera de Biología Química y Laboratorio, periodo enero 2017- agosto 2017 - Buñay Llangari, Héctor Fabián (2017)
The research was carried out in the carrer of Chemical Biology and Laboratory, with the objective of analyzing the Interdisciplinarity as a learning methodology to link Zoology with Microbiology with the students of fourth semestre, whose purpose is to improve students´ competences. The problema is the weak application of the interdisciplinary to link Zoology and Microbiology, the work is base don the theory of constructivist learning subjects of the context. The research study is non-experimental because the variables were not manipulated so that the phenomena were observed in the natural context. The type of research was of field and bibliographical, the level of research is descriptive, and the research method Inductive and Deductive, for this was taken into account to all the 19 students of fourth semestre and the interest of the survey and the instrument the questionnaire, to obtain information with closed questions. In conclusión, it is established the importance of the interdisciplinarity for the integration of the experimental sciences in the learnning of Zoology and Microbiology, due to the evolution of education with the intervention of the integration of knowledge.